Database for Monitoring the Technical Condition of Structures as an Integral Part of Industrial Safety - Bogachenko, S. V.; Shatov, S. V. (Science and Transport Progress, 2024)
Purpose. Development of a database designed to systematization and store information on the technical condition of industrial structures based on the results of periodic visual and instrumental surveys. Methodology. The information system includes a database, a database management system and an application programme. The most appropriate type of database for monitoring the technical condition of structures is a relational structure. The database model covers owners, buildings, structures, quantitative and qualitative parameters of defects and damage, strength indicators of building structures and tilt of industrial structures. Findings. Structural query language was used in the process of developing a database for monitoring the technical condition of industrial facilities. The created database "Monitoring" includes interconnected tables that provide holistic and efficient storage of information. The tables are linked using foreign keys, which provides easy access and data management. The tables are conditionally divided into those that users fill in and those that are filled in in accordance with legislative and regulatory documents at the stage of database creation. This approach to building a database ensures structured storage of information on the technical condition of buildings, taking into account regulations and legislation. The integration of tables filling in by users and pre-filled tables creates a system that increases the efficiency of monitoring the technical condition of industrial structures. Originality. The scientific novelty of the proposed database lies in an innovative approach to structuring and integrating various types of data related to the technical condition of industrial structures. The system offers an effective combination of data from different formats and sources into a single information space and will further provide a comprehensive analysis of the condition of building structures, which is one of the key factors of industrial safety. Practical value. It is intended to improve the efficiency of industrial structures maintenance and exploitation safety, and provides tools for storing the results of monitoring the condition of building structures.